Slideboardin': Testing, circuit training, and training tips (Part 2) - Publow, B. (1999)
About constructing a well designed training program with the slideboard for speed skaters and inline skaters. - Benefits for skaters - Slide board Workouts - Performance Evaluation - Design - Procedure - Analysis - Training the Lactic Acid System - Circuit Training